Multiphase 2006
DOI: 10.1615/ihtc13.p12.60
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Optimization of the Method of Cooling of a Massive Casting of Ductile Cast-Iron

Abstract: An original application of ANSYS simulating the forming of the temperature field of a massive casting from ductile cast-iron during the application various methods of its cooling using steel chills. The numerical model managed to optimize more than one method of cooling but, in addition to that, provided serious results for the successive model of structural and chemical heterogeneity, and so it also contributes to influencing the as solidified microstructure. The file containing the acquired results from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The solidification and cooling of a classically cast (i.e. gravitationally poured) casting (ingot) and simultaneous heating of the mould and chills is, from the viewpoint of thermokinetics, a very complicated case of 3D transient heat and mass transfer [1][2][3][4][5]. In systems comprising the casting (ingot), the mould, chills and environment, all three kinds of heat transfer take place.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The solidification and cooling of a classically cast (i.e. gravitationally poured) casting (ingot) and simultaneous heating of the mould and chills is, from the viewpoint of thermokinetics, a very complicated case of 3D transient heat and mass transfer [1][2][3][4][5]. In systems comprising the casting (ingot), the mould, chills and environment, all three kinds of heat transfer take place.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The importance of considering strength variability of DI has been shown by Olofsson and Svensson (2013) and Shirani and Härkegård (2014). Kavicka et al (2010) found out correlations between local solidification time and local microstructure for large DI castings. Wessén and Svensson (1996) developed a model for ferrite growth in DI castings, and Donelan applies a method for modelling the microstructural and mechanical properties of ferritic DI to thick-walled casting (Donelan 2000).…”
Section: Introductionmentioning
confidence: 99%
“…After successful validation of a model, numerical simulation can be an efficient tool for relatively fast verification of the designed corrections in the production technology. Nowadays, by using numerical simulations, it is possible to predict the complete process, from the technology plan [7,8,9] through castings casting [10,11], including solidification [12][13][14], stress states [13][14][15][16][17], defects prediction [13,14,18,19] and resulting metallographic structure of a casting [19][20][21].…”
Section: Introductionmentioning
confidence: 99%